Economical feeding of male dairy calves - Lima, Carlos Rodrigues; Faria, Ernesto Vater; Laun, George Friedrich (Pesquisa Agropecuaria Brasileira, 2014)
Studies were conducted in an attempt to determine an economic feeding method for male dairy calves. Crossbred animals (European vs. Indian) were used. Three treatments were compared in a completely randomized design experiment: 1-(control), the calves were fed whole milk during the first 150 days of age at the level of 1/10 of their liveweight and also received 100 g of concentrate mixture for each 10 kg of Iiveweight above 50 kg: 2- whole milk, in the same proportion as treatment 1, during the first 28 days. The calves were gradually weaned between 29 and 56 days of age, by substituting a concentrate mixture for milk in the following way: 5th week, 4 -3 kg of milk; 6th week, 3 -2 kg of milk; 7th week, 2 -1 kg of milk; 8th week, 1-0 kg of milk; starting at 14 days of age the calves had free access to the concentrate mixture: 3- whole milk in the same proportion as treatments 1 and 2 during the first 35 days of age; between 36 and 56 days of age the whole milk was gradually substituted by soybean milk; after 56 days of age, the calves received soybean milk and concentrate mixture at the same levels as the control group. In treatment 2 the results showed higher liveweight gain at lower cost. The results of treatment 3 were not considered good. No significant difference was found (P<0,05) between treatment 2 and 3 as far as liveweight gains were concerned.